2015
DOI: 10.1080/00224499.2014.1002124
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role, Gender Identity and Sexual Orientation in CAIS (“XY-Women”) Compared With Subfertile and Infertile 46,XX Women

Abstract: The perception of gender development of individuals with complete androgen insensitivity syndrome (CAIS) as unambiguously female has recently been challenged in both qualitative data and case reports of male gender identity. The aim of the mixed-method study presented was to examine the self-perception of CAIS individuals regarding different aspects of gender and to identify commonalities and differences in comparison with subfertile and infertile XX-chromosomal women with diagnoses of Mayer-Rokitansky-Küster-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 70 publications
0
16
1
Order By: Relevance
“…Our result is in agreement with the findings of Brunner et al ., in which five of 11 participants with cAIS chose the gender/sex category of ‘other’. However, an overlap of participants might be possible as they are both German studies . These results are different to previous studies, in which female gender identity and role were established and maintained in all individuals diagnosed with cAIS .…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Our result is in agreement with the findings of Brunner et al ., in which five of 11 participants with cAIS chose the gender/sex category of ‘other’. However, an overlap of participants might be possible as they are both German studies . These results are different to previous studies, in which female gender identity and role were established and maintained in all individuals diagnosed with cAIS .…”
Section: Discussioncontrasting
confidence: 90%
“…The term ‘disorders of sex development’ is controversial within interdisciplinary teams and affected individuals as it is perceived as pathologizing and might be confused with aberrant sexuality or gender identity . The authors therefore prefer ‘differences of sex development’, which was introduced by other researchers . Depending on the impact of androgens, the functional impairment of the gonads and the reproductive system, DSD can have different effects on the individual's body and health.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, recent literature has begun to challenge this strongly established view of nearly exclusive heterosexual behaviors in women with CAIS. A recent report by Brunner and colleagues () indicated that 46,XY women compared with other females with infertility conditions showed increased tendencies of nonheterosexual preference and behavior, evidence that is out of line with previously established views of fully heterosexual outcomes in women with CAIS. These findings, although limited to a small sample size (n = 11 CAIS), raise an interesting topic for further investigation that could identify additional influences guiding sexual preference and perhaps identity in 46,XY women, aside from their inability to respond to male‐sex hormone.…”
Section: Sexual Behaviors and Gender Identitymentioning
confidence: 82%
“…Once again however, recent reports have begun to suggest that this theory is not as concrete as previously thought. A growing body of literature and case reports has identified gender dysphoria and cross‐gender feelings in CAIS individuals at rates higher than have been established (Kulshreshtha et al, ; T'Sjoen et al, ; Brunner et al, ). The role of social and initial medical decisions associated with CAIS cases may be a contributing factor in these results because, as stated by Tom Mazur, “the best predictor of adult gender identity in CAIS, PAIS (partial androgen insensitivity syndrome) and micropenis is initial gender assignment” (Mazur, ).…”
Section: Sexual Behaviors and Gender Identitymentioning
confidence: 99%
“…In fact, in CAIS patients, with complete lacking function of the androgen receptor, female gender identity is usually reported indicating that masculinization of gender identity depends of androgen exposure during foetal period [90]. However, two cases of male gender identity in CAIS individuals have been reported in literature [91][92][93], questioning the role of androgen receptor in brain masculinization. Observations from other intersex conditions-such as 5-alpha-reductase-2 deficiency-lead to assume a potential role of pubertal hormones in the development of gender identity.…”
Section: The Shaping Effect Of Sex Hormones and Involved Genes On Bramentioning
confidence: 99%